Предмет: Алгебра,
автор: elmirafaizova
решите уравнение х(х-1)-х(х-3)=12
Ответы
Автор ответа:
0
х2 - х- х2+3х=12
-х+3х=12
2х=12
х=6
-х+3х=12
2х=12
х=6
Автор ответа:
0
и еще поблагодари
Автор ответа:
0
2х-х-2х+3х=12
-х+3х=12
2х=12
Х=12:2
Х=6
Может так
-х+3х=12
2х=12
Х=12:2
Х=6
Может так
Автор ответа:
0
потом -х=12-3
Автор ответа:
0
-х=9
Автор ответа:
0
х=-9
Автор ответа:
0
за такой ответ -9, тебе сразу оценку 2 поставят! ВОТ НЕВНИМАТЕЛЬНЫЙ (АЯ)
Похожие вопросы
Предмет: Информатика,
автор: vikafedorova19
Предмет: Математика,
автор: dzokerbroska
Предмет: Информатика,
автор: girlitosha2002
Предмет: Химия,
автор: SashaLP
Предмет: Математика,
автор: Κγĸγрγℑκα